Technical Variation in Scientific Model (Al-Academy, 2017)
The present study tackles the scientific model and the mechanisms of operating in the formation of the image of the artistic work to create a scene that cares for the aesthetic decoration through raw and techniques and employing them to express the aesthetic values that care for what is not familiar and deviation from the familiar in the visual exhibition and the care for the employment of the technical abilities, lighting, and sound as well as the employment of multiple materials. The research presents the objectives of his study in the exhibition hall of Natural History Museum (University of Baghdad) to create an aesthetic and expressive state at the same time. Then, in the theoretical framework the researcher traces the experiments of the contemporary world art and operating with the scientific and artistic models in the exhibiting halls of international museums; the technical role in building any artistic work through the dialogue of the accumulated expertise of the artist’s imagination and his ability to form ideas and manifest them by choosing the test for the aesthetic solutions of the various raws. The research, after that, operated with applied samples of the research including the Dodo bird and beehive sample that are placed for display in the Museum. The function content and expression were taken into consideration for each sample whether in formal building or in the content, to create a harmony among the raws and ideas to be conveyed to the viewer in a manner that achieves the trace of amazement and feel of the aesthetic values and knowledge simultaneously. In the fourth section the results and the conclusions which the researcher comes up findings like: the technical variation in the scientific model contributes to enrich the relation of the raws and the items of the artistic work and opens the way for experimentation towards the diverse use of the materials and techniques. That forms the main role in the accumulation of the aesthetic expertise of the artist. The variation of the scientific model in the museums by the use of different techniques like the collage, assembly, photographs, ready-made form, light, sound, piercing , excavation, sculpture, embalmment, and the employment of electronic devices, computers, monitors and video shows. All that has contributed to the development of the scientific and artistic museums alike